The Spatial-Institutional Architecture of Firms' Innovative Behaviour - Eric de Noronha Vaz; Teresa de Noronha Vaz; Peter Nijkamp (Tinbergen Institute, 2013)
In recent decades there have been an enormous number of studies about innovation systems, partly inspired by a great interest among policy makers in search for a solid scientific foundation and professional support to identify appropriate development strategies. Despite different perspectives, most studies highlight knowledge creation and innovation as the major drivers of change and growth. This consensus disappears, however, as soon as the complexity of innovation and knowledge are taken into consideration. Innovation goes far beyond new product or process development on account of its interactive nature, while knowledge often surpasses the firms' internal mechanisms, because, frequently, it is a spatially endogenous characteristic. The present paper aims to offer a refreshing contribution to the above discussion and represents an effort to develop a novel model able to answer how institutions are relating to each other, drawing networks of innovation. The available database comprises an extensive set of Portuguese innovative firms, spatially identified and able to engage in spatial connectivity in order to understand where and how strong the links are for innovation in Portugal, and to analyse the respective levels of geographical concentration or dispersion.
Keywords: O31; D21; 330; innovation; firms